Kualitas Pelayanan Pegadaian Mempengaruhi Loyalitas Melalui Kepuasan Nasabah (Studi: Perum Pegadaian Unit Timoho Di Kota Yogyakarta) - Wendri Rusli (Universitas Ahmad Dahlan, 2012)
This study aimed to examine the effect of service quality and customer satisfaction to increase customer loyalty. As the pawn that depends on public trust. pawn shops are required to provide optimum service to always put quality of service so that customers will feel satisfied and secure in the world of mortgage transactions. Approaches include: tangible reliability, responsiviness, assurance, emphaty. Data used in this study is the primary data obtained through questionnaire method. The population in this study was all customers Pawnshop Timoho unit Jogjakarta in 2012. Not all populations studied so that the sampling done by accidental sampling technique. Number of samples taken are as many as 100 customers. Data analysis technique used is multiple regressions with SPSS. Proof testing results show that SERVQUAL dimensions tangible, reliability, responsiviness, assurance, emphaty, has a positive and significant influence on customer satisfaction.